Constructing Cu1-Ti dual sites for highly efficient photocatalytic hydrogen evolution. (1st December 2022) - Feng, Yajie; Wang, Yang; Wang, Kaiwen; Ban, Chaogang; Duan, Youyu; Meng, Jiazhi; Liu, Xue; Ma, Jiangping; Dai, Jiyan; Yu, Danmei; Wang, Cong; Gan, Liyong; et al.
Abstract: Constructing dual sites is promising to break scaling relations between the adsorption energetics of reaction intermediates and ultimately improves the activity and selectivity due to the synergistic effect. However, it is a grand challenge to precisely form a dual-site configuration with one metal site adjacent to another active site. Loading single atoms onto oxides with pre-introduction of surface oxygen vacancies may be an alternative strategy to overcome such challenge. Motivated by our theoretical calculations that the dual sites formed by single Cu atoms and unsaturated Ti sites on TiO2 enables a higher activity towards hydrogen evolution from water splitting than corresponding single site, we successfully synthesized a Cu1 -Ti dual-site catalyst by depositing Cu single atoms on TiO2 nanoparticles with abundant surface oxygen vacancies. The designed target catalyst significantly outperforms the benchmark Pt nanoparticle decorated TiO2 with a high and stable activity towards photocatalytic hydrogen production. Graphical Abstract: ga1 Highlights: Theoretical calculations revealed that Ovs promote water dissociation and single Cu atoms promote hydrogen evolution. The designed target catalyst exhibited extraordinarily high activity and excellent stability for photocatalytic H2 evolution. The method provide a paradigm that precisely combines single atoms with substrate metal sites to generate active dual sites.